THE ANALYSIS OF FIGURATIVE LANGUAGE IN SONG LYRIC BY INDINA MENZEL - Fachri Yunanda; Yossy Kevin Parulian Pardede; Novia Esra Wati; Angelika Sara Deaparin; Aprilia Eka Krisdayanti Tafonao (Jurnal Basataka (JBT), 2021)
In writing songs, songwriters often use figurative language. In this study, the researchers analyzed the figurative language contained in three of Idina Menzel's songs, namely "Let It Go", "I Got My Love to Keep Me Warm" and "For The First Time in Forever". The objective of this study is to find out the type of figurative language used and the meaning represented by the figurative language in the three songs of Idina Menzel. The theoretical benefit of this study is that this study can be a reference to other researchers who do similar study. While practical benefits are divided into two, for students and teachers. For students, research may be useful to increase understanding and knowledge of figurative language; increase students literacy motivation, especially figurative language observation; and students become more creative and critical. For teachers, this research can be useful as a reference in learning, especially figurative language; gain new experiences in different learning situations; and maximize teacher satisfaction because students' language skills are increasing. This study is a descriptive qualitative approach. Results of study found that there were eleven figurative languages used by songwriters, namely hyperbole as much as 31.3%, repetition 25.4%, personification 9.8%, metaphor, simile, and alliteration 5.8%, onomatopoeia, irony, and idiom. 3.9%, and finally imagery and pleonasm 1.9%. In addition, the songwriter also uses connotative and denotative meanings in the three songs.